Phase II study of dose‐adjusted gemcitabine, dexamethasone, cisplatin, and rituximab in elderly relapsed diffuse large B‐cell lymphoma patients. Issue 2 (15th October 2020) - Yamasaki, Satoshi; Kada, Akiko; Choi, Ilseung; Iida, Hiroatsu; Sekiguchi, Naohiro; Harada, Naoko; Sawamura, Morio; Shimomura, Takeshi; Komeno, Takuya; Yano, Takahiro; Yoshida, Isao; Yoshida, Shinichiro; et al.
Abstract: High‐dose chemotherapy and autologous stem cell transplantation (ASCT) are too toxic for elderly patients with relapsed or refractory diffuse large B‐cell lymphoma (DLBCL). Therefore, effective and tolerable regimens for elderly patients are urgently needed. The present phase II study assessed the efficacy and safety of dose‐adjusted therapy with gemcitabine, dexamethasone, cisplatin, and rituximab (GDP‐R) in this population. ASCT‐ineligible elderly patients with relapsed or refractory DLBCL received dose‐adjusted GDP‐R in each 28‐day cycle for up to six cycles. The primary endpoint was overall response rate (ORR), and secondary endpoints were complete response (CR) rate, progression‐free survival (PFS), and safety. Thirty‐three patients were enrolled and received dose‐adjusted GDP‐R. The median age was 75 years (range: 68‐87 years). The ORR was 82.8% (90% confidence interval [CI], 67.1‐93.0%), with a CR rate of 58.6% (90% CI, 41.7‐74.1%). At a median follow‐up of 20.9 months, the 2‐year PFS rate was 46.8% (90% CI, 30.7‐61.5%) and the 2‐year overall survival rate was 63.2% (90% CI, 45.8‐76.3%). The most frequently observed grade 4 adverse events were neutropenia (63.6%), thrombocytopenia (57.6%), and lymphocytopenia (39.4%). Dose‐adjusted GDP‐R is a promising salvage regimen for ASCT‐ineligible elderly patients with relapsed DLBCL after rituximab‐containing chemotherapy and warrants further investigation.